Comparison Of Different Types Of Sago Starch Dispersion And On Mechanical Properties Of Biodegradable NR Latex Films - Norfaizal, Nurhafiz Syaza (Universiti Sains Malaysia, 2018)
The increase in Natural Rubber (NR) latex products, particularly gloves in global consumption results in enormous amounts of discarded NR latex products and contributed to the solid waste disposal problems. The biodegradability of NR latex can be improved by addition of sago starch dispersion which commonly prepared using anchoid as dispersing agent. The purpose of this studies were to investigate the utilisation of different dispersing agents, sodium alginate and Carboxy Methyl Cellulose (CMC) in preparation of sago starch dispersions in order to improve the sago starch particle size distribution and biodegradability of the NR latex films. The sago starch anchoid, sago starch sodium alginate and sago starch CMC dispersions were prepared by using ball milling method, respectively before adding at 10 phr loading into NR latex compounds. The compound was pre-vulcanised at 70°C until chloroform number 2 was achieved. The effect of addition of different types of sago starch dispersions on mechanical properties (tensile properties and tear strength), zeta potential, swelling index, crosslink density of NR latex films were obtained. NR latex with sago starch sodium alginate dispersion give good dispersion stability and better mechanical properties (tensile properties and tear strength) compared to NR latex with sago starch CMC dispersion. The swelling index NR latex with sago starch sodium alginate decreased indicated that higher crosslink density. The post processing (leaching, aging and biodegradation) of the NR latex with different sago starch dispersions were obtained. Based from the results obtained, the utilisation of sodium alginate dispersing agent can be used as replacement of anchoid dispersing agent in preparing the sago starch dispersions which gives comparable properties of biodegradable NR latex films